THE RELATIONSHIP OF THE SYNCHRONIZATION BETWEEN THE HITTING ARM MOTION AND THE TAKE-OFF FOOT IN TERMS OF ANGULAR AND LINEAR VELOCITY WITH THE ACCURACY OF THE FLOAT SERVE IN VOLLEYBALL FOR JUNIORS - Firas Chasib Khalaf; Mustafa Ismail Aseen; Qahtan Mohammed jbbar (Proximus Journal Publishing, 2026)
The study aimed to identify and quantify the motor synchronization between the hitting arm and the take-off foot during the execution of the float serve. It also sought to measure the angular velocity of the hitting arm and the linear (peripheral) velocity of its distal segment at the moment of ball contact, through pre- and posttesting of the research sample. The researcher hypothesized that there would be a statistically significant correlation between the synchronization of the hitting arm and the take-off foot and the angular velocity of the arm. A second hypothesis proposed the presence of a statistically significant correlation between the synchronization of the hitting arm and the take-off foot and the peripheral velocity of the distal end of the arm. The research population was defined as the players of the Naft Maisn Club for the 2024 season, consisting of (6) players. Based on the findings, the researchers recommended adopting specialized training exercises to develop motor synchronization between the hitting arm and the take-off foot, using training methods that emphasize timing and temporal precision in performance. They also emphasized focusing training on the phases of generating angular velocity and its transfer through the kinetic chain—from the foot, through the trunk, and ultimately to the hitting arm. The researcher concluded that there is a strong and direct correlation between the synchronization of the hitting arm and the take-off foot, indicating that temporal coordination between these motor actions is a decisive factor in achieving accuracy in the float serve among youth players. The results showed that the greater the motor synchronization between the hitting arm and the take-off foot, the lower the temporal dispersion in performance, which positively influenced the stability of the ball's trajectory and its accuracy in reaching the targeted zone on the opposite court
Keywords: Synchronization; Hitting Arm; Take-Off Foot; Angular